Potential Hypoglycemia in Patients With Type 2 Diabetes Mellitus Due to Drug Interactions in Citra Husada Hospital - Elisa wardatul awaliya; shinta mayasari; khrisna agung cendekiawan (LPPM Universitas dr. Soebandi, 2024)
Diabetes mellitus (DM) is a metabolic disorder disease characterized by an increase in blood glucose due to decreased insulin secretion by pancreatic beta cells, insulin disorders or resistance. The main risks that are commonly found in every patient diagnosed with DM disease include hypoglycemia. In a study conducted at a public hospital in Jakarta, 186 incidents of interaction of antidiabetic drugs with other drugs that have hypoglycemia potential with a moderate clinical significance level of 83.8% were found. The potential for drug interactions in DM patients is still very frequent. This can be caused by the number of drugs that are often used (Polipharmacy or multiple drug therapy). The purpose of this study is to identify the potential for hypoglycemia in type 2 DM patients due to drug interactions at Citra Husada Jember hospital. This type of research is qualitative research with retrospective data collection. The design of this study uses a cross-sectional design. The population of this study is 662 medical record data of outpatients with type 2 diabetes for the period of January – December 2022. Data analysis uses univariate analysis. In this study, most patients have the potential to experience hypoglycemia.